Biophysics of Infection - Leake, Mark C. (Advances in Experimental Medicine and Biology, 2016)
This book describes modern biophysical techniques that enable us to understand and examine dynamic processes of infection at the molecular level. Cutting-edge research articles, laboratory protocols, case studies and up-to-date reviews cover topics such as single-molecule observation of DNA replication repair pathways in E. coli; evolution of drug resistance in bacteria; restriction enzymes as barriers to horizontal gene transfer in Staphylococcus aureus; infectious and bacterial pathogen biofilms; killing infectious pathogens through DNA damage; bacterial surfaces in host-pathogen interactions; bacterial gene regulation by riboswitches; transcription regulation in enterobacterial pathogens; the bacterial flagellar motor; initial surface colonization by bacteria; Salmonella Typhi host restrictions; as well as monitoring proton motive force in bacteria; microbial pathogens using digital holography; mathematical modelling of microbial pathogen motility; neutron reflectivity in studying bacterial membranes; force spectroscopy in studying infection and 4D multi-photon imaging to investigate immune responses. The focus is on the development and application of complex techniques and protocols at the interface of life sciences and physics, which increase the physiological relevance of biophysical investigations.